Analysis of Economic and Social Demographic Factors That Influence the Dependency Ratio on the Island of Sumatra - Dicky Randika Aji; Emi Maimunah; Dedy Yuliawan; Zulfa Emalia (Lafadz Jaya Publisher, 2023)
This study aims to analyze the influence of education level, the proportion of married women who use birth control, life expectancy, per capita income, labor force on the dependency ratio. The method and analytical tools used in this research are panel data regression. The dependent variable used is the dependency ratio and the independent variables are education level, proportion of married women who use birth control, life expectancy, per capita income, labor force. The best model obtained is the Random Effect Model. The research results show that regardless of education level, the proportion of married women who use birth control, life expectancy, per capita income, labor force have a positive and significant effect on the dependency ratio on Sumatra Island.